2015
DOI: 10.3109/07420528.2015.1102925
|View full text |Cite
|
Sign up to set email alerts
|

Latent activity rhythm disturbance sub-groups and longitudinal change in depression symptoms among older men

Abstract: Activity rhythms disturbances and depression often co-occur among older adults. However, little is known about how activity rhythm disturbances themselves co-occur, or how disturbances to multiple aspects of the activity rhythm relate to depression over time. In the current study, we performed a Latent Class Analysis to derive sub-groups of older men (total n=2933, mean age=76.28, SD=5.48) who shared similar patterns of activity rhythm disturbances (defined as extreme values of modeled activity rhythm paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 43 publications
8
66
0
Order By: Relevance
“…Initially (7), we only found depression risk associated with a measure of rhythm robustness or regularity (the pseudo F-statistic). But our later work (11) revealed that low pseudo F-statistics tended to only be found when overall activity was also low, and that this occurred in diverse groups – those with earlier, normative, and later timing.…”
Section: Summary Of the Evidence That Rars Represent A Depression Rismentioning
confidence: 80%
See 3 more Smart Citations
“…Initially (7), we only found depression risk associated with a measure of rhythm robustness or regularity (the pseudo F-statistic). But our later work (11) revealed that low pseudo F-statistics tended to only be found when overall activity was also low, and that this occurred in diverse groups – those with earlier, normative, and later timing.…”
Section: Summary Of the Evidence That Rars Represent A Depression Rismentioning
confidence: 80%
“…Only limited research has investigated whether RARs are prospectively associated with the development of depression symptoms (7, 11). Initial findings indicate that different combinations of RAR characteristics (or RAR profiles) may increase depression risk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent UK Biobank study suggested a lower relative amplitude in those with a retrospectively determined lifetime incidence of major depressive disorder, bipolar disorder, and mood instability [21•]. A longitudinal study in elderly men reported that both a late acrophase alone and the combination of an early acrophase with a dampened 24-h activity rhythm amplitude were associated with a faster increase in depressive symptoms over time [56]. Additionally, a genome-wide association study (GWAS) including 71,500 participants reported a possible association between genetic risk of a low relative amplitude and mood disorders [45•].…”
Section: Depressionmentioning
confidence: 99%